Phase equilibrium diagram of Y-Cu-Sb system at 870 K - Romaka, L.; Stadnyk, Yu.; Romaka, V.V.; Zelinskiy, A.; Klyzub, P.; Horyn, A. (Physics and Chemistry of Solid State, 2023)
The interaction of the components in the Y-Cu-Sb ternary system was investigated using the methods of X-ray phase analysis, microstructure, and energy-dispersive X-ray spectroscopy in the whole concentration range at 870 K. At the temperature of investigation Y-Cu-Sb system is characterized by the formation of three ternary compounds: Y3Cu22Sb9 (Dy3Cu20+xSb11-x structure type, space group F-43m, a=1.6614(3) nm), Y3Cu3Sb4 (Y3Au3Sb4 structure type, space group I-43d, а=0.95357(5) nm), YCuSb2 (HfCuSi2 structure type, space group P4/nmm, a=0.42580(1), c=0.98932(3) nm). The solubility of copper in the binary compound YSb (NaCl structure type) extends up to 8 at. %.